Consequences of Parental Job Loss on the Family Environment and on Human Capital Formation - Evidence from Plant Closures - Eva Maria Mörk; Anna Sjögren; Helena Svaleryd (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the consequences of mothers' and fathers' job loss for parents, families, and children. Rich Swedish register data allow us to identify plant closures and account for non-random selection of workers to closing plants by using propensity score matching and controlling for pre-displacement outcomes. Our overall conclusion is positive: childhood health, educational and early adult outcomes are not adversely affected by parental job loss. Parents and families are however negatively affected in terms of parental health, labor market outcomes and separations. Limited effects on family disposable income suggest that generous unemployment insurance and a dual-earner norm shield families from financial distress, which together with universal health care and free education is likely to be protective for children.
Keywords: I12; J10; 330; parental unemployment; workplace closure; family environment; child health; human capital formation